2018
DOI: 10.3390/ijerph15102325
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Psychological Well-Being: A Multidimensional Measure

Abstract: Over the last few years, different theoretical approaches have emerged advocating for a positive understanding of adolescence, recognizing it as a stage characterized by plasticity, the acquisition of competences and the achievement of satisfactory levels of well-being and positive adjustment. Based on Ryff’s multidimensional model of psychological well-being, this study aims: (1) to develop an adjusted measuring instrument for adolescents (Brief Scale of Psychological Well-Being for Adolescents), as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 96 publications
2
49
0
6
Order By: Relevance
“…To this, we must add the fact that the majority of studies on children's and adolescents' SWB are of a cross-sectional nature, which acts as a hindrance to gaining in-depth knowledge on how the evolutionary changes that take place throughout their development affect or are affected by their SWB. Some years ago, various cross-sectional studies started revealing that this supposed stability might not be taking place [11], a result that was later confirmed when scales with more response options were included (0-10-point scales) and particularly, when involving longitudinal studies. Two main results were observed.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…To this, we must add the fact that the majority of studies on children's and adolescents' SWB are of a cross-sectional nature, which acts as a hindrance to gaining in-depth knowledge on how the evolutionary changes that take place throughout their development affect or are affected by their SWB. Some years ago, various cross-sectional studies started revealing that this supposed stability might not be taking place [11], a result that was later confirmed when scales with more response options were included (0-10-point scales) and particularly, when involving longitudinal studies. Two main results were observed.…”
Section: Introductionmentioning
confidence: 98%
“…However, the question of whether there are changes in SWB during late childhood and early adolescence has only recently received the attention of researchers working in this field, despite it being a period in which wellbeing would appear to have its own idiosyncrasies with respect to previous and subsequent age groups [11]. Among the reasons for this is that most research has focused on adult samples, in which a relative stability in their levels of SWB has been observed, although with certain oscillations at certain periods of life [12].…”
Section: Introductionmentioning
confidence: 99%
“…It may be considered a characteristic of successful people [6]. Viejo et al [33] found a person's satisfaction with their own achievement is an important antecedent of psychological well-being. Schumpeter [25] described the entrepreneur as a person who has the will to conquer and succeed.…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Third, the contradiction in results might reflect on the connection between psychological wellbeing and parameters of age and gender. Several studies demonstrate that girls tend to have higher estimates of psychological wellbeing than boys in both gifted and general groups [11,20,21]. On the contrary, gifted girls may have lower levels of psychological wellbeing [22], especially in the cases of math-related giftedness [23].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, gifted girls may have lower levels of psychological wellbeing [22], especially in the cases of math-related giftedness [23]. Also, several authors argue that psychological wellbeing decrease starting from middle to older teen ages [21,24,25]. According to the meta-analysis by Т. Jones, however, for gifted children age-related decline in psychological wellbeing was not statistically significant [11].…”
Section: Introductionmentioning
confidence: 99%